Impact of microplastics on the in situ, high-resolution of key nutrient dynamics at the soil-water interface in rice fields - Jiang, Yizhen; Zhu, Xiaoyan; Zhang, Siyuan; Yang, Jingang; Lu, Yongzheng; Wang, Ying (Frontiers in Environmental Science, 2023)
Introduction: Microplastics are characterized by their small size, widespread distribution, and durability, present a significant environmental risk. Despite their omnipresence in terrestrial and aquatic systems, the potential consequences on nutrient cycling remain under-investigated. Microplastics have emerged as a focal point of current research, presenting both a challenge and a frontier in environmental science. Methods: This study explores the effects of microplastics on the high-resolution, in situ distribution and exchange dynamics of key nutrients, nitrogen (N) and phosphorus (P), at the soil-water interface in rice paddies, utilizing the Diffusive Gradients in Thin-films (DGT) technique. Results: Our results reveal distinct spatial distribution patterns for N and P across the soil-water interface. Labile phosphorus (P) concentrations were significantly higher in the soil than in the overlying water, whereas DGT-NO3− concentrations exhibited the inverse trend. Different microplastic concentrations notably impacted DGT-NO3− (P = 0.022) and DGT-NH4+ (P = 0.033), with an increase between 27.79% and 150.68%. Moreover, different particle sizes significantly influenced NH4+. Interestingly, paddy soil acted as a “source” for labile P and a “sink” for NH4+ and NO3−. Discussion: These insights provide valuable insights into the interactions between microplastics and nutrient cycles at the soil-water interface, and assess the effects on nutrient migration and transformation. The outcomes of this study will contribute to an improved understanding of the broader ecological implications of microplastic pollution in agricultural settings. It will also provide a foundation for the development of strategies to manage and mitigate the impacts of microplastic pollution in agricultural soils, particularly in rice dominated agroecosystems.